STUDENTS’ ARGUMENTATION TEXT ANALYSIS IN INDONESIA USING APPRAISAL APPROACH (APPRECIATION) - Atika Lisamawati; Wahyu Rima Agustin; Dessy Dwijayanti (PT Akselerasi Karya Mandiri, 2024)
This research is qualitative descriptive research with a fixed case study that has the following objectives: to describe students' opinions in the text about